MENGATASI PERMASALAHAN BELAJAR SISWA KELAS X PEMASARAN 3 SEMESTER 1 MELALUI KONSELING EKLEKTIF DENGAN PERILAKU ATTENDING DI SMK NEGERI 1 TASIKMALAYA - Aisah, Enur Siti (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
The many problems faced by students regarding their study habits which are still considered ineffective are identified with problems that occur at school, including; low academic achievement, lack of interest in studying, violation of rules, truancy, often late, quarreling, difficulty adapting, shy, timid, withdrawn, dirty talk and rude behavior. In practice, handling student problems within the framework of guidance and counseling is resolved through individual counseling and group counseling. Various theories have been put forward by experts regarding the approaches or techniques used by counselors during the counseling process. Basically, counseling approaches/techniques are divided into three (Moh. Surya: 1988). namely: directive, non-directive and eclectic counseling techniques. Eclective Counseling Techniques are a combination of two Directive and Non-Directive Counseling techniques. Researchers combine the goodness of these two counseling techniques, develop and apply them in practice according to students' learning problems with an orientation towards relationship techniques between counselors and clients, namely Eclectic Techniques with Attending Behavior. Based on the background above, the problem in this research can be formulated as follows; 1) What is the influence of Eclective Counseling techniques with Attending Behavior in overcoming student problems? 2). What is the influence of Eclectic Counseling techniques with the Attending Behavior of teachers as counselors in increasing student achievement. This research is Classroom Action Research (PTK) which was carried out in 3 (three) cycles, each cycle carried out in 4 (four) stages, namely planning, implementation, observation and evaluation and reflection. From the results of the research and discussion described in the previous chapter, it can be concluded that the Eclective Attending Approach is an effective step to overcome student problems. The Eclective Attending Approach makes it easy to change attitudes for students who have problems because learning problems can be overcome through communication in the child's own language and Selective Techniques and Attending Behavior are suitable for use and development by teachers, and further research needs to be conducted